Correction: Initiating Binary Metal Oxides Microcubes Electromagnetic Wave Absorber Toward Ultrabroad Absorption Bandwidth Through Interfacial and Defects Modulation - Li, Fushan; Wu, Nannan; Kimura, Hideo; Wang, Yuan; Xu, Ben Bin; Wang, Ding; Li, Yifan; Algadi, Hassan; Guo, Zhanhu; Du, Wei; Hou, Chuanxin (Nano-Micro Letters, 2025)
Cobalt nickel bimetallic oxides (NiCo2O4) have received numerous attentions in terms of their controllable morphology, high temperature, corrosion resistance and strong electromagnetic wave (EMW) absorption capability. However, broadening the absorption bandwidth is still a huge challenge for NiCo2O4-based absorbers. Herein, the unique NiCo2O4@C core–shell microcubes with hollow structures were fabricated via a facile sacrificial template strategy. The concentration of oxygen vacancies and morphologies of the three-dimensional (3D) cubic hollow core–shell NiCo2O4@C framework were effectively optimized by adjusting the calcination temperature. The specially designed 3D framework structure facilitated the multiple reflections of incident electromagnetic waves and provided rich interfaces between multiple components, generating significant interfacial polarization losses. Dipole polarizations induced by oxygen vacancies could further enhance the attenuation ability for the incident EM waves. The optimized NiCo2O4@C hollow microcubes exhibit superior EMW absorption capability with minimum RL (RLmin) of −84.45 dB at 8.4 GHz for the thickness of 3.0 mm. Moreover, ultrabroad effective absorption bandwidth (EAB) as large as 12.48 GHz (5.52–18 GHz) is obtained. This work is believed to illuminate the path to synthesis of high-performance cobalt nickel bimetallic oxides for EMW absorbers with excellent EMW absorption capability, especially in broadening effective absorption bandwidth. Highlights: 1 3D cubic hollow core–shell NiCo2O4@C composites were synthesized. 2 Oxygen vacancies were introduced into the prepared composites. 3 Ultrabroad effective absorption bandwidth of 12.48 GHz was obtained. 4 The absorption performance mechanism of NiCo2O4/C composites was investigated.